S45 Evaluating the sensitivity and specificity of active neutrophil elastase as a biomarker for bacterial infection in subjects with copd. (15th November 2016) - Thulborn, SJ; Akram, N; Mistry, V; Brightling, CE; Moffitt, K; Ribeiro, D; Bafadhel, M
Abstract : Introduction: COPD is a neutrophilic disease, with the majority of subjects having a sputum neutrophil percentage of >60%. Neutrophil elastase (NE) is a serine proteinase, secreted by neutrophils and macrophages during inflammation and has a role in the destruction of bacteria within the host. New advancements now allow accurate assessment of active protease levels in complex biological samples. We sought to investigate if active NE could be used as a biomarker for bacterial infection in subjects with COPD. Methods: NE was quantified using ProteaseTag TM active NE Immunoassay (ProAxsis, Belfast) from cell-free sputum supernatant from 31 COPD subjects (20 Males; mean age 65, range 45 to 81) at stable state and during an exacerbation. Bacterial infection was defined as ≥10 7 CFU/mL in sputum. Subject demographics, sputum cell differential counts and polymerase chain reaction (PCR) for respiratory pathogens were measured. Results: Active NE was higher during an exacerbation compared to stable state (fold difference (95% CI) 0.50 (0.22 to 0.78), p = 0.001) (Figure 1 ). NE correlated with total sputum neutrophils (p < 0.0001, r = 0.48) and total bacterial load measured by CFU/mL (p < 0.01, r = 0.39) and qPCR (p < 0.05, r = 0.33). When looking at the main respiratory pathogens no correlations were seen between H. influenzae (p = 0.43, r = −0.11), S. aureus (p = 0.34, r = −0.14) or S. pneumonia (p = 0.11, r = 0.23); however a correlation was seen between NE and M. catarrhalis (p = 0.01, r = 0.36). NE has an area under the receiver operator curve of 0.72 [0.58 to 0.85] to identify a bacterial infection with a sensitivity and specificity of 67.74% and 67.86% at a NE cut off of 2335ng/mL. Conclusion: Active NE is elevated during a COPD exacerbation compared to baseline. Active NE is associated with neutrophilic inflammation and bacteria; and may be a viable biomarker for bacterial infection in COPD.